Simplify 9x+3y−6−5x+4y−3

.

1 answer

To simplify the expression \( 9x + 3y - 6 - 5x + 4y - 3 \), we can combine like terms.

  1. Combine the \( x \) terms: \[ 9x - 5x = 4x \]

  2. Combine the \( y \) terms: \[ 3y + 4y = 7y \]

  3. Combine the constant terms: \[ -6 - 3 = -9 \]

Putting it all together, we have: \[ 4x + 7y - 9 \]

Thus, the simplified expression is: \[ \boxed{4x + 7y - 9} \]

Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions